2011
DOI: 10.1590/s1676-26492011000100006
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and experimental epilepsy

Abstract: Introduction: Disturbances in intrauterine environment can have harmful effects on the fetus and pathological consequences persisting throughout adolescence and adulthood. Protein restriction during the prenatal period has a significant impact on growth and development of the central nervous system. Food restriction increases the risk of neurological disorders such as epilepsy. Objective: To relate the programming model by malnutrition and its implications in experimental epilepsy. Material and methods: There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…Early life nutritional programming is based on the observation that nutritional and environmental changes, or lack thereof, can reset the developmental path during a critical period of life, when tissues still have plasticity and are in a higher proliferating state and differentiating phase (de Moura et al, 2008;Gomes et al, 2011). Research has demonstrated that nutritional programming can occur via epigenetics and can take place as early as late gestation (Moisa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Early life nutritional programming is based on the observation that nutritional and environmental changes, or lack thereof, can reset the developmental path during a critical period of life, when tissues still have plasticity and are in a higher proliferating state and differentiating phase (de Moura et al, 2008;Gomes et al, 2011). Research has demonstrated that nutritional programming can occur via epigenetics and can take place as early as late gestation (Moisa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%